Pengetahuan Remaja Putri Tentang Kebersihan Alat Kelamin Pada Saat Menstruasi di SMPN 25 Pekanbaru - Bukit, Rosmeri br (SCIENTIA JOURNAL, 2019)
Treatment during menstruation needs to be done because during menstruation the reproductive organs are very susceptible to infection. Lack of maintaining cleanliness during menstruation, for example, using inappropriate underwear, how to clean the wrong reproductive organs from the back to the front, not changing sanitary napkins during menstruation. Reproductive tract infections can be caused by the entry and proliferation of germs such as bacteria, fungi, viruses, and parasites. Impacts that can occur if a person is not paying attention to the cleanliness of genetial organs during menstruation, which are several venereal diseases such as cervical cancer, vaginal discharge, genital skin irritation, allergies, inflammation, and urinary tract The purpose of this study was to find out the description of young women knowledge about the cleanliness of genitals during menstruation at Pekanbaru 25 Junior High School. This type of research is quantitative in descriptive design. This research was conducted at Pekanbaru 25 Junior High School on March 21-22 2019 with a population of 199 eighth grade students and a sample of 199 respondents. Data collection techniques are simple random sampling, measuring instruments used questionnaires and univariate data analysis. Based on the research that has been carried out at Pekanbaru 25 Junior High School, 146 respondents (73%) were well-informed, while 53 respondents (27%) were not knowledgeable. It can be concluded that the knowledge of young women about the cleanliness of genitals during menstruation at Pekanbaru 25 Junior High School is well-informed.